Reducing crude protein content in the diet of lactating dairy cows improved nitrogen-use-efficiency and reduced N excretion in urine, whilst having no obvious effects on the rumen microbiome - Agalu W. Zeleke; Nicholas J. Dimonaco; Katie Lawther; Anna Lavery; Conrad Ferris; Jon Moorby; Sharon A. Huws (Journal of Animal Science and Biotechnology)
Abstract Background Nitrogen-Use-Efficiency (NUE) in lactating dairy cows, defined as milk nitrogen (N) output as a proportion of N consumed, is low, with the majority of excess N excreted in manure. Excreted N can be lost to the environment as ammonia gas leading to environmental acidification and nutrient enrichment of sensitive habitats, and to watercourses contributing to aquatic eutrophication. While there is much evidence that NUE can be improved by reducing the crude protein (CP) content of dairy cow diets, the long-term impacts of feeding lower protein diets on cow performance and the rumen microbiome are less well understood. This study examined the effects of reducing the CP contents of dairy cow diets on cow performance, NUE, the relationship between NUE and residual feed intake (RFI), and the rumen microbiome. Results Dietary CP content did not affect feed intake, milk yield or milk composition (P > 0.05), except for milk urea N (MUN), which increased with increasing diet CP content (P < 0.05). The mean NUE was 34%, 34% and 31% for the LCP (low-protein, 15%), MCP (medium-protein, 16%), and HCP (high-protein, 17%) diets, respectively. RFI was negatively correlated with NUE (r = −0.57, P < 0.001). The rumen ammonia-N concentrations increased with increasing dietary CP; however, the ruminal pH and volatile fatty acid (VFA) content of the rumen fluid remained constant. Predicted urinary N excretion was greater in the HCP and MCP diets than in the LCP diet. Reducing dietary CP content in dairy cow diets did not affect microbial composition, diversity and functional profiles. The family Bacteroidaceae was more abundant in HE (high-efficiency) cows, whereas the Methanobacteriaceae and the genus Methanobrevibacter were more abundant in LE (low-efficiency) cows. Additionally, propanoate metabolism, cysteine and methionine metabolism and amino acid biosynthesis pathways were more abundant in HE cows, whilst the methane (CH4) metabolism pathway was upregulated in LE cows. Conclusions The results demonstrate that diet CP can be reduced with no loss in cow performance, but with an associated reduction in N excretion. The abundance of microbial populations differed between low and high efficiency cows, which may contribute to the differences in efficiency observed. Graphical abstract